2009
DOI: 10.1007/s11671-009-9405-8
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles and Graphitic Carbon Through Thermal Decomposition of a Silver/Acetylenedicarboxylic Salt

Abstract: Spherically shaped silver nanoparticles embedded in a carbon matrix were synthesized by thermal decomposition of a Ag(I)/acetylenedicarboxylic acid salt. The silver nanoparticles, which are formed either by pyrolysis at 300°C in an autoclave or thermolysis in xylene suspension at reflux temperature, are acting catalytically for the formation of graphite layers. Both reactions proceed through in situ reduction of the silver cations and polymerization of the central acetylene triple bonds and the exact temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
9
0
4
Order By: Relevance
“…Here we will focus on the formation of carbon species in order to elucidate the nucleation of TiO2 particles since, as based on the literature, it is believed that a graphitic layer plays a crucial role on the nanoparticle formation. The precursors (I), (II), (III), (IV), (V), and (VI) were annealed at 400 C and their Raman spectra are shown in Figure 1, where the typical D and G graphite bands [18,41,42,43,44] are observed. These bands are not clearly defined in some cases, as observed for the macromolecular precursor (III) and (V).…”
Section: Resultsmentioning
confidence: 99%
“…Here we will focus on the formation of carbon species in order to elucidate the nucleation of TiO2 particles since, as based on the literature, it is believed that a graphitic layer plays a crucial role on the nanoparticle formation. The precursors (I), (II), (III), (IV), (V), and (VI) were annealed at 400 C and their Raman spectra are shown in Figure 1, where the typical D and G graphite bands [18,41,42,43,44] are observed. These bands are not clearly defined in some cases, as observed for the macromolecular precursor (III) and (V).…”
Section: Resultsmentioning
confidence: 99%
“…As it can be seen, the absorption spectrum corresponding to carbon nanotubes shows a peak at 252 nm, which is the characteristic peak of functionalized carbon nanotubes (C=C bond) [25] . The slight shifts are observed in both characteristic peaks of CNT and AgNPs toward lower wavelengths after reduction of Ag ions (Figure 1), this is due to the coupling of the surface plasmon electrons with the sp 2 carbon atoms of the graphitic layers [26] . Also, by increasing the biomass weight from 3 to 11 g, this peak shifts from 415 to 428 nm.…”
Section: Uv-visible Spectrum Analysismentioning
confidence: 98%
“…Wostek-Wojciechowska et al, Dallas et al, and Jung et al stated that thermal decomposition could be performed as either thermolysis or pyrolysis [ 33 – 35 ]. Dallas et al did the pyrolysis of his silver nanoparticles at a temperature of 300°C [ 34 ]. They also carried out thermolysis in both solid and liquid states [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dallas et al did the pyrolysis of his silver nanoparticles at a temperature of 300°C [ 34 ]. They also carried out thermolysis in both solid and liquid states [ 34 ]. In the case of Wostek-Wojciechowska et al, they reported that better nanoparticles were obtained when in solution than in the solid state [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation